Intrafiber lipid droplets in swimming skeletal muscle of stranded cetaceans in Canary islands - Sierra Pulpillo, Eva María; Arbelo Hernández, Manuel Antonio; Mendez, M.; Alves Godinho,Ana; Andrada Borzollino, Marisa Ana; Jáber Mohamad, José Raduán; Espinosa De Los Monteros Y Zayas, Antonio; Fernández Rodríguez, Antonio Jesús (2005)
The present study is focused on the analysis of swimming skeletal muscle samples (longissimus dorsi) from 15 different species of 86 stranded cetaceans in Canary Islands from 1996 to April 2004. The purpose of this study was to evaluate the presence of spherical intrafiber lipid droplets to explain the aerobic capacity of skeletal muscles under the hipoxic conditions of diving. The previously fixed tissue in 10% neutral buffered formalin solution was post fixed in 1% osmium tetroxide, dehydrated in graded ethanol series and embedded in paraffin. Sections (5 mm in thickness) were cut, treated with picric acid for 24 hours and stained with hematoxilyneosin. As result 19 of the 86 animals (22%) belonged to 7 of the 15 species of cetaceans presented different degree of intrafibrilar doplets with the osmium tetroxide method. The percentages exhibited for each species were the following: Globicephala macrorhynchus (n=8 ) 38%; Kogia breviceps (n=5) 20%; Kogia sima (n=2) 50%; Mesoplodon densirostris (n=2) 100%; Physeter macrocephalus (n=7) 43%; Stenella frontalis (n=12) 8% and Ziphius cavirostris (n=10) 70%. According to the results described above we may conclude that swimming skeletal muscle of deep, long-duration divers species showed a greater amount of lipid intrafiber droplets that swimming skeletal muscle of short-duration divers species.